Pembuktian Paulus sebagai Penulis Surat Ibrani Berdasarkan Bukti Internal - Joy Sopater Wasiyono (SOTIRIA (Jurnal Theologia dan Pendidikan Agama Kristen), 2020)
Abstract: The Epistle to the Hebrews is an epistle that has sparked a lot of controversies. The most common debates are those relating to authorship. Among the issues of authorship, the most provocative of debate is the discussion about the author. The most important tool in the investigation of the author of writing is the internal evidence of the writing itself. This research is focused on proving Paul as the author of Hebrews based on internal evidence. The research method used is descriptive qualitative non-experimental research with exegetic and biblical approaches to texts that are considered to have significance in the proof of the author to the Hebrews. After careful examination of the text of The Epistle to the Hebrew, is found 25 internal evidence for the author of the Hebrews. This internal evidence was subsequently used to prove Paul's authorship of the Hebrews. Abstrak Surat Ibrani adalah surat yang memicu banyak kontroversi. Perdebatan paling umum adalah yang berhubungan dengan kepenulisannya. Di antara persoalan-persoalan kepenulisan, yang paling memicu perdebatan adalah pembahasan tentang siapa penulisnya. Alat bantu terpenting dalam penyelidikan penulis sebuah tulisan adalah bukti-bukti internal dari tulisan itu sendiri. Penelitian ini difokuskan untuk membuktikan Paulus sebagai penulis surat Ibrani berdasarkan bukti-bukti internal. Metode penelitian yang digunakan adalah penelitian kualitatif deskriptif non eksperimental dengan pendekatan eksegesis dan biblika terhadap teks-teks yang dianggap memiliki signifikansi dalam pembuktian penulis surat Ibrani. Setelah dilakukan penelitian yang cermat terhadap teks surat Ibrani, maka diperoleh 25 bukti internal penulis surat Ibrani. Bukti-bukti internal ini selanjutnya digunakan untuk membuktikan kepenulisan Paulus atas surat Ibrani.